Morbilidad y mortalidad ocasionada por el tipo de lesión que sufren las víctimas de trauma en la ciudad de Machala - Tinoco Romero, César David (2020)
Severe trauma is the sixth leading cause of death and the fifth leading disability in the world. Approximately 5 million people died from this cause. In 2014, Ecuador presented 5768 reported cases, of which the most frequent were: traumatic brain injury (TBI), airway obstruction, respiratory or cardiac arrest, and massive bleeding, becoming the third cause of death so it is considered appropriate to carry out this study to determine trauma-related morbidity and mortality and obtain statistical data that will serve as the basis for establishing control, management and intervention strategies by the organizations involved to control this health problem. For this reason, a descriptive, quantitative approach and cross-sectional study was carried out at the IESS Machala General Hospital. This research aims to determine the morbidity and mortality caused by the type of injury in victims who suffer trauma, analyzing relation to sex, age, and traumatic findings with all the patients who suffered trauma and went to the emergency service, 119 patients were studied where the general morbidity was 95.80% (n = 114) and deaths 4.20% (n = 5). Morbidity in the female sex was 15.97% (n = 19) and male 79.83% (n = 95). The TBI registered mortality of 4.20% (n = 5), in the male sex. Morbidity from trauma was: TBI 19.32% (n = 23), thoracic 8.40% (n = 10), abdominal 20.17% (n = 24), pelvic 2.52% (n = 3), skeletal muscle 42.86% (n = 51) and 2.52% spinal cord trauma (n = 3). In conclusion: men were the most affected in morbidity (mean age 43.4 years) and mortality (mean age 38.2 years). Keywords: Epidemiology; Age; Sex; Trauma